2018
DOI: 10.4317/jced.55050
|View full text |Cite|
|
Sign up to set email alerts
|

Criteria and treatment decisions in the management of deep caries lesions: Is there endodontic overtreatment?

Abstract: BackgroundThe aim of this study was to investigate the diagnostic criteria and treatment decisions in the management of deep caries lesions (DCLs). The null hypothesis tested was that DCLs are managed according to the current scientific evidence.Material and MethodsA total of 288 dentists were contacted directly or by mail, and 125 (43%) were included in the study. Dentists were requested to answer a questionnaire about the routine approach to the diagnosis and treatment of DCLs. Logistic regression analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…In fact, a recent study investigating the preferred management methods of Finish dentists for DCLs in adult patients (24), has found that less invasive treatments are being selected into clinical practice by the majority of dentists in Finland. Similar results have been reported in a survey carried out to a sample of Spanish dentists (25).…”
Section: Discussionsupporting
confidence: 90%
“…In fact, a recent study investigating the preferred management methods of Finish dentists for DCLs in adult patients (24), has found that less invasive treatments are being selected into clinical practice by the majority of dentists in Finland. Similar results have been reported in a survey carried out to a sample of Spanish dentists (25).…”
Section: Discussionsupporting
confidence: 90%
“…The number of views was found to be significantly higher in pulpotomy contents, probably because of the applicability of this procedure to deciduous teeth in pediatric dentistry and the specialized nature of the pulp capping treatment for young permanent teeth with open apices that are usually referred to experts. In general, it has been documented that vital pulp treatment procedures for the fully developed permanent teeth are less popular and root canal treatment is preferable among dentists, a fact that may be reflected by the lower number of views regarding direct pulp cap videos [ 23 24 ]. Regarding patients, low popularity of dental pulp capping videos may be attributed to the specialized nature of these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this review advocate step wise partial caries removal [26] or selective caries removal [17] as the more favorable technique. Although, generally, for the authors'-complete caries Discussion removal has worked well in the past where the soft carious tissue is removed till hard dentinal tissue is encountered [35] and then covered with Calcium hydroxide liner and Glass Ionomer at a single visit followed by Composite layer on the same visit or subsequent visit.…”
Section: Safetymentioning
confidence: 99%
“…But the authors' current practice may not be factual and deemed as "over-treatment" [18,35] as new research on cariology [18,35] has refuted our myth and we like the 80% dentists as compared to 8.8 [35] believed in total excavation and the study [35] reflects on encouraging more dentists to take up cariology CPD courses as literature supports selective/ partial caries removal being definitely better than complete caries removal to prevent a pulp exposure [38,43] and unnecessary endodontic treatment [39]. The need to incorporate evidenced based dentistry via CPD courses and reading peer reviewed journals is important to educate ourselves in using less invasive strategies to treat deep carious lesions and not allow just our beliefs of the past gained through didactic methods, influence better decision making in our dental practices.…”
Section: Safetymentioning
confidence: 99%